Respublikinių suvestinių katalogų tyrimo klausimu - Kastanauskaitė, Danutė (Knygotyra, 1972)
Our present-day life makes us rationalize the work of the library. One of the ways to implement it is the Union Catalogue system. The Republic Union Catalogue (hereafter-RUC) is a constituent part of it. In the Soviet Union much importance is attached to the compilation and investigation of the catalogues.In the present article an attempt is made to tackle the most urgent problems of RUC theory, organization and practical application. It is based on the results of RUC investigation that appeared in the Soviet press during the last decade.What concerns the theoretical aspect of RUC the question of accurately defining its notion is discussed. Educational literature should throw more light on the role that state, republic and V. Lenin libraries play in organizing RUC.The organization part of RUC include such problems as relations between republic and all-union catalogues, drawing up appropriate instructions, investigation of applying technical means in compiling RUC.It is stated in the article that possibilities to introduce RUC should be analyzed not only in prospect, but at present tiine as well. The functions of RUC as a catalogue should be brought out more clearly.With this in view a futher investigation of RUC organization is encouraged. It is desirable that the results of RUC investigation should he given a full coverage in all-union press, that reports and articles on the subject should be more scientific.The conclusion is drawn that the results of RUC theoretical and practical investigation should be summed up and developed into a wide-range scientific paper.It is expected that RUC investigation would contribute much to the development of scientific-technical system of information. It would speed up national and international communications.